Effect of deep-level defect density of the absorber layer and n/i interface in perovskite solar cells by SCAPS-1D - Chowdhury M.S.; Shahahmadi S.A.; Chelvanathan P.; Tiong S.K.; Amin N.; Techato K.; Nuthammachot N.; Chowdhury T.; Suklueng M. (Elsevier B.V., 2023)
In this paper, Solar Cell Capacitance Simulator-1D (SCAPS-1D) was used to study the absorber layer defect density and n/i interface of perovskite solar cells versus various cell thickness values. The planar p-i-n structure was defined as PEDOT:PSS/Perovskite/CdS, and its performance was simulated. Power conversion efficiency >25% can be achieved at <1014 cm?3 defect density and >400 nm thickness of absorber layer, respectively. The study assumed 0.6 eV Gaussian defect energy level below the perovskite's conduction band with a characteristic energy of 0.1 eV. These conditions resulted in an identical outcome on the n/i interface. These results show constraints on numerical simulation for correlation between defect mechanism and performance. 2019 The Authors